Pelatihan Self Healing Untuk Mengurangi Burnout Konselor Sekolah - Syarif, Dina Fariza Tryani; Karyanti, Karyanti; Fatchurahman, M. (Universitas Nusantara PGRI Kediri, 2022)
Training held in Community Service Stimulus Community Partnership Program (PKMS) is intended for counselors. The implementation of Self Healing is designed to reduce Burnout School Counselor, as a solution to problems faced by employees who tend to experience psychological stress, such as stress which may hinder the performance of school counselors. For that counselors and psychologists can facilitate Burnout Prospective school counselors. Organizational changes, such as restructuring and mergers, can result in higher levels of job stress and demands, such as psychological uncertainty about how the change will affect their position, role ambiguity i.e., unclear expectations. Employees indicated that one of the outcomes of psychological stress was Burnout. Burnout is a psychological process produced by work stress that is inseparable and results in emotional exhaustion, personality changes, and decreased feelings of achievement. The training activities were carried out for two days from October 09 to October 10, 2021. The training participants consisted of 20 counselors. The team evaluates the program and the results of self-healing using an instrument in the form of a scale. The scale is used as a pre-test and post-test. Based on the results of the pre-test and post-test ontraining, self-healing participants at the beginning of the activity experienced burnout in the high and medium categories, after thetreatment was carried out self-healing, based on the results of the post-test. burnout counselordecreased in the medium and low categories. It can be concluded thattraining self-healing can reduce burnout counselor.